Do symbol and device matter? The effects of symbol choice of fake news flags and device on human interaction with fake news on social media platforms. (July 2023) - Figl, Kathrin; Kießling, Samuel; Remus, Ulrich
Abstract: Social media platforms need to respond effectively to the accusation of distributing fake news. Thus, this study investigates the extent to which different types of fake news flags (Pinocchio symbol, stop symbol, caution symbol) and the type of device (smartphone vs. PC) used to engage with (fake) news posts influence believability, user engagement, and cognitive elaboration. We test for such differences in an experimental design using data from 256 participants exposed to artificially generated Facebook posts on political (fake) news. Results confirm that fake news flags provide an effective countermeasure against believing in fake news. However, the semantic priming effect of different warning symbols used, which is inextricably intertwined with the device on which fake news is consumed, makes the difference between effective and less effective fake news flags. Smartphones do not per se increase (fake) news believability compared to PCs, but our findings suggest that stronger warnings may be required on smartphones than on PCs. Overall, this study provides a rich and contextualized understanding of fake news flags and user interaction with fake news, pointing to some important practical implications for social media platform designers. Highlights: Different symbol designs of warning labels that highlight fake news change users' reactions to social media posts. Caution symbols were most effective in reducing the believability, and stop symbols in increasing the amount of time spent. Compared to PCs, smartphones reduce the time users spend reading a fake news post, while likes and dislikes remain constant. Smartphones do not per se increase the believability of fake news posts on social media in comparison to PCs. The effectiveness of warning labels that highlight fake news depends on whether users see them on a smartphone or a PC.